Caricatured Figure of Glutton in M. Amis’s Discourse: A Pragmatic-Semantic Perspective - S. A. Petrenko; A. Ph. Petrenko; S. V. Tishchenko (Научный диалог)
This study investigates the pragmatic-semantic aspects of the hyperbolized representation (caricaturization) of gluttony within the discursive space of M. Amis’s novel “Money: A Suicide Note.” It analyzes both direct nominations and metaphorically reinterpreted linguistic resources that contribute to the creation of a parodic image of the fat man and glutton at the sentence level and within a broader intratextual context. The underlying mechanisms that construct a typified situation of gluttony and its consequences are unveiled. The use of cognitive dissonance is characterized as a device that aids in shaping the comic figure of the protagonist in the novel. The author emphasizes Amis’s iterative approach to constructing a caricatured archetypal image of the hedonist and glutton through a variety of lexico-semantic, stylistic, and contextually-cognitive tools, noting their high discursive density. Cognitive-linguistic mechanisms for representing the theme of gluttony in a caricatural and hyperbolized manner are identified. The findings open new horizons for exploring pragmatic-semantic resources and the cognitive-discursive potential of verbal manifestations of the contemporary issue of selfish lifestyles. The connotative and emotive multidimensionality of the caricatured verbal image is defined.